DAKWAH DIGITAL DALAM PENGUATAN KAPASITAS SOSIAL KOMUNITAS MUSLIM (PROGRAM PENGABDIAN KEPADA MASYARAKAT BERBASIS SERVICE-LEARNING DI MASJID AGUNG ANAS MAHFUD, LUMAJANG) - Achmad Arifulin Nuha; Alhimni Fahma; Harry Purwanto (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The development of digital media provides new opportunities for mosques to perform da‘wah while simultaneously strengthening community empowerment. Mosques are no longer merely places of worship, but also function as centers of social communication and capacity building for Muslim communities through digital platforms. This article aims to describe and analyze a Service Learning–based community engagement program focused on strengthening digital da‘wah at the Anas Mahfud Grand Mosque in Lumajang, Indonesia. The program employed a participatory approach through mentoring in digital da‘wah management, capacity building for mosque administrators and volunteer media teams, development of contextual digital content, and optimization of social media platforms as tools for congregational communication and empowerment. Data were collected through participant observation, interviews, documentation, and qualitative evaluation of congregational responses and participation in digital spaces. The results indicate that strengthening digital da‘wah contributed to a significant increase in congregational participation, expansion of community social networks, and reinforcement of the mosque’s role as a center for community empowerment. Within one month, Facebook followers increased from approximately 2,000 to over 5,000, while YouTube subscribers rose from around 100 to 821. These findings confirm that mosque-based digital da‘wah is an effective community engagement strategy for strengthening the social capacity of Muslim communities in the digital era.